2023
DOI: 10.1158/2326-6066.c.6550200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from The IKZF1–IRF4/IRF5 Axis Controls Polarization of Myeloma-Associated Macrophages

Abstract: <div>Abstract<p>The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was found that CRBN-CRL4 degrades IKZF1 through UPS, and IKAROS family zinc finger 1 (IKZF1) is a transcription factor that regulates macrophage chromatin, which positively regulates IRF4 and negatively regulates IRF5 (Mougiakakos et al, 2021;Oh et al, 2018). IRF4/IRF5 expression affects the polarization state of TAMs, with IRF4 playing a major role in the induction of M2-like polarization in macrophages and IRF5 being highly expressed in M1-like polarized macrophages and mediating efficient TH1 and TH17 responses (Krausgruber et al, 2011;Nam & Lim, 2016;Satoh et al, 2010).…”
Section: Crbn-crl4/ikzf1 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that CRBN-CRL4 degrades IKZF1 through UPS, and IKAROS family zinc finger 1 (IKZF1) is a transcription factor that regulates macrophage chromatin, which positively regulates IRF4 and negatively regulates IRF5 (Mougiakakos et al, 2021;Oh et al, 2018). IRF4/IRF5 expression affects the polarization state of TAMs, with IRF4 playing a major role in the induction of M2-like polarization in macrophages and IRF5 being highly expressed in M1-like polarized macrophages and mediating efficient TH1 and TH17 responses (Krausgruber et al, 2011;Nam & Lim, 2016;Satoh et al, 2010).…”
Section: Crbn-crl4/ikzf1 Axismentioning
confidence: 99%
“…Studies at this stage showed that the immunomodulatory drug IMiD regulates the IRF4/IRF5 axis by mediating CRBN-CRL4 degradation of IKZF1, which shifts TAMs from M2-like polarization to M1-like polarization (Mougiakakos et al, 2021). The development of drugs based on CRBN-CRL4 to reprogram TAMs is very promising.…”
Section: Crbn-crl4/ikzf1 Axismentioning
confidence: 99%